The Speech Act of Thanking in Cicero’s Correspondence (Annual of the Faculty of Philosophy in Skopje, 2017)
The research subject of this paper is the speech act of thanking in Cicero’s correspondence. The analysis of realization patterns of this speech act indicates evident differences in the expressions that used to do this act in the letters to different addresses. In the letters that are the product of a personal private and familial interaction, thanks is expressed with the expressions gratum [mihi est], mihi gratissimum est, me pergratum fecisti and te amo/amamus. However, in the letters that are the product of a private epistolary interaction, but at a lower level of intimacy between the correspondents, the thanking is usually done with the performative expression gratias (maximas) tibi ago. The expressions of gratitude in the chosen corpus also differ in other aspects: in the letters that are the product of a distanced epistolary interaction the speech act of thanking is always elaborated in greater detail and is almost always followed by an expression that indicates the strength of the correspondents ’ friendship or the virtues that the addressee has as a person. In several cases in this type of letters the act of thanking itself incorporates the parenthesis ut debeo, which suggests that with this speech act the author is attempting to meet the aspect of a socially desirable behaviour. One of the strategies of expressing gratitude in the letters that are the product of private epistolary interaction is the “refusal ” to say thanks. This strategy derives from the perception that the act of expressing gratitude is a formality, which is superfluous in friendships that have developed ad summam benevolentiam.
Keywords: THE SPEECH ACT OF THANKING; CICERO; LETTERS